Diagnosis and Management of Carcinoma of the Larynx - Tri Hedianto; Afia Nuzila Fadhlina; Riva Satya Radiansyah (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Introduction. Laryngeal carcinoma is a major malignancy of the head and neck, with a global incidence of 58.67%. This malignancy commonly affects men over the age of 50 with a significant history of smoking. The diagnosis is frequently delayed until advanced stages, especially in low-resource settings. The study aimed to present a case series of laryngeal carcinoma and evaluate the diagnosis and management. Method. A case series and literature review involving patients diagnosed with laryngeal carcinoma who underwent assessment through to definitive treatment. Results. We report four male patients aged 51–67 years who presented with longstanding hoarseness and respiratory distress. All underwent tracheotomy followed by micro-laryngoscopic biopsy, which confirmed squamous cell carcinoma. Tumor staging was determined via CT imaging ranging from T2N0M0 to T4aN2M0. Treatment for all patients consisted of total laryngectomy combined with either selective or modified radical neck dissection. Histopathology revealed well to moderately differentiated squamous cell carcinoma in each case. Postoperative outcomes were favourable, with no major early complications. Conclusion. The diagnosis and management of laryngeal carcinoma remain challenging, particularly in resource-limited settings. Early detection is crucial for improving treatment outcomes and overall prognosis. Enhancing public awareness, strengthening multidisciplinary approaches, and expanding diagnostic infrastructure are essential to optimize patient care and survival.